2000
DOI: 10.1007/bf02817563
|View full text |Cite
|
Sign up to set email alerts
|

Rare non-albicans candida species detected in different clinical diagnoses

Abstract: In working on the incidence of yeasts we excluded from the tested set C. albicans, C. krusei, C. parapsilosis and C. tropicalis on the basis of morphological and biochemical properties. We found 16 rare species of yeasts: C. claussenii (16), C. guilliermondii (10), C. robusta (9), C. pulcherrima (8), C. zeylanoides (4), C. glabrata (3), C. lusitaniae (3), C. catenulata (2), C. mesenterica (2), C. utilis (2), C. freyschussii, C. intermedia, C. kefyr, C. lipolytica, C. mogii, C. pseudotropicalis (1 for each). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…Sequence analysis of the D1/D2 domain also showed that C. haemulonii type II differs from C. haemulonii type strain by 15% sequence divergence in the D1/D2 domain (Kurtzman & Robnett, 1997), but C. haemulonii type II is yet to be described as a separate species. Of the two species of the sister clade, C. mogii, originally isolated from 'miso', was also associated with human infections (English & Atkinson, 1974;Dorko et al, 2000) and C. tolerans was isolated from Hibiscus flowers . NRRL Y-27702 (AY640205) has been isolated from the gut of an unidentified geometrid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence analysis of the D1/D2 domain also showed that C. haemulonii type II differs from C. haemulonii type strain by 15% sequence divergence in the D1/D2 domain (Kurtzman & Robnett, 1997), but C. haemulonii type II is yet to be described as a separate species. Of the two species of the sister clade, C. mogii, originally isolated from 'miso', was also associated with human infections (English & Atkinson, 1974;Dorko et al, 2000) and C. tolerans was isolated from Hibiscus flowers . NRRL Y-27702 (AY640205) has been isolated from the gut of an unidentified geometrid.…”
Section: Resultsmentioning
confidence: 99%
“…NRRL Y-27702 (AY640205) has been isolated from the gut of an unidentified geometrid. Of the two species of the sister clade, C. mogii, originally isolated from 'miso', was also associated with human infections (English & Atkinson, 1974;Dorko et al, 2000) and C. tolerans was isolated from Hibiscus flowers .…”
Section: Resultsmentioning
confidence: 99%
“…13 At least 16 other Candida spp. are known to occur in humans, 12 mostly associated with other severe medical conditions. Candida spp.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The vast majority of human infections are C. albicans 12,13 and presumably the same applies to avian patients. are causally related to alimentary tract disease or are opportunistic pathogens secondary to altered host immunity or luminal microbial conditions, such as occurs with antibiotic administration.…”
Section: Luxol Fast Blue Sticky Tape Preparation Of Cultured Rhizopmentioning
confidence: 99%
See 1 more Smart Citation